PENGARUH WORK-LIFE BALANCE TERHADAP KEPUASAN KERJA DENGAN STRES KERJA SEBAGAI VARIABEL MEDIASI (Studi pada Karyawan Bank Indonesia Kantor Perwakilan Jawa Tengah) - Hamna Satriansyah ; Agung Nugroho Adi, SE., MM., MM.HRM (Manajemen FEB - UB, 2019)
This study aims to determine the effect of work-life balance on job satisfaction with work stress as a mediating variable, at Bank Indonesia employees at the Central Java Representative Office. This type of research is explanatory research, which focuses on explaining the relationship between variables, namely the independent variable, namely work-life balance (X), the dependent variable is job satisfaction (Y), and the mediating variable is work stress (M). Respondents in this study were all employees of the Bank Indonesia Representative Office in Central Java, amounting to 116 people. The method of data collection is done through the distribution of questionnaires and interviews as primary sources and literature studies as secondary sources. Test instruments in this study using validity and reliability tests. The method of data analysis uses path analysis to find out the direct and indirect effects. The results of the study show that work-life balance directly influences work stress and job satisfaction significantly. Job stress directly has a significant effect on job satisfaction, work-life balance does not affect job satisfaction through work stress. Keywords: work-life balance, job stress, job satisfaction